Pattern of Analgesic use and Perception of Pain Management by Health Care Workers in a Medical Facility - Rebecca O. Soremekun, Oladipupo K. Ogunjuyigbe, Ebele E. Onwuchuluba (Journal of Applied Pharmaceutical Science, 2016)
Background and objectives: Though analgesics are the main stay in pain management, physicians' knowledge on pain assessment and treatment modalities could affect the management. This study sought to evaluate pattern of analgesics prescription, healthcare professionals' knowledge and perception of pain and its management in a secondary healthcare facility. Methods: This was a descriptive retrospective review of 16,365 prescriptions of patients within the medical facility for six months to evaluate drugs used in pain management. Cross-sectional survey of 50 healthcare professionals' knowledge and perception of pain management in the facility was also carried out through the use of a questionnaire. Results: 4,323 (26.42%) prescriptions had no pain medication. 36% prescriptions had multiple pain medications and non-opioid analgesics (85.4%) were the most commonly prescribed. Dosage forms prescribed were oral (91.38%) >Injectables (5.08%) >dermal (2.9%). 64% of health workers perceive pain as closely connected with an underlying illness but were not familiar with standard pain management guideline. Conclusion: There is a high volume of analgesic use and the non-opioids are the most commonly prescribed in this facility. Health care practitioners connect pain and some other illnesses but standard pain management guidelines were not used.
Keywords: Pain management,Analgesics,Prescribing Pattern,Pain perception.